2
$\begingroup$

Find the Fourier series for $f(x) := |\sin(x)|$ and the sum of $\sum_{n=1}^{\infty} \frac {(-1)^{n+1}} {4n^2-1}$.

I have computed $$c_n = \frac 1 {2\pi} \int^{\pi}_{-\pi} |\sin(x)|e^{-inx} dx = \frac 1 {2\pi} \int^{\pi}_{0} |\sin(x)|e^{-inx} + |\sin(-x)|e^{-in(-x)} dx = \frac {1} {\pi} \frac {1} {n^2-1} ((-1)^{n+1} -1)$$

However, this doesn't correspond that well with the sum of the series I must find. What have I done wrong ?

$\endgroup$
  • $\begingroup$ A good way for you and us to find your mistake (if there is one) is to completely write your calculation. $\endgroup$ – user37238 May 20 '14 at 8:09
  • $\begingroup$ Did you think about the substitution $m=2n$? $\endgroup$ – Fabian May 20 '14 at 8:22
  • $\begingroup$ try to find $x$ s.t all the terms beside those on the even spots will become 0. $\endgroup$ – Snufsan May 20 '14 at 8:35
  • $\begingroup$ Similar question here math.stackexchange.com/questions/467787/… $\endgroup$ – Graham Hesketh May 20 '14 at 16:08
2
$\begingroup$

The exponential Fourier series for this particular $f(x)$ is \begin{align} |\sin(ax)| = \sum_{n= -\infty}^{\infty} c_{n} e^{-i nx}, \end{align} where \begin{align} c_{n} = \frac{1}{2\pi} \int_{-\pi}^{\pi} |\sin(ax)| \ e^{-i nx} dx. \end{align} This integral can be calculated as follows. \begin{align} c_{n} &= \frac{1}{2\pi} \int_{-\pi}^{\pi} |\sin(ax)| \ e^{-i nx} dx \\ &= \frac{1}{2\pi} \int_{-\pi}^{0} |\sin(ax)| \ e^{-i nx} dx + \frac{1}{2\pi} \int_{0}^{\pi} |\sin(ax)| \ e^{-i nx} dx \\ &= \frac{1}{2\pi} \int_{0}^{\pi} |\sin(-ax)| \ e^{i nx} dx + \frac{1}{2\pi} \int_{0}^{\pi} |\sin(ax)| \ e^{-i nx} dx \\ &= \frac{1}{\pi} \int_{0}^{\pi} \sin(ax) \cos(nx) dx \\ &= \frac{1}{2\pi} \int_{0}^{\pi} \left[ \sin(a+n)x + \sin(a-n)x \right] dx\\ &= \frac{1}{2\pi} \left[ \frac{2a}{a^{2} - n^{2}} - \frac{\cos(a\pi + n \pi)}{a+n} - \frac{\cos(a\pi - n \pi)}{a-n} \right] \\ c_{n} &= \frac{a}{\pi (a^{2} - n^{2})} \left[ 1 - (-1)^{n} \cos(a\pi) \right]. \end{align} From this the Fourier series is \begin{align} |\sin(ax)| = \frac{a}{\pi} \sum_{-\infty}^{\infty} \frac{(1 - (-1)^{n} \cos(a\pi))} {\pi (a^{2} - n^{2})} \ e^{-i nx}. \end{align} The summation can be changed and is seen in the following. \begin{align} \sum_{-\infty}^{\infty} b_{n} e^{-i nx} &= \sum_{-\infty}^{-1} b_{n} e^{-i nx} + b_{0} + \sum_{1}^{\infty} b_{n} e^{-i nx} \\ &= b_{0} + \sum_{n=0}^{\infty} \left( b_{-n} e^{i nx} + b_{n} e^{-i nx} \right). \end{align} From this it is seen that \begin{align} |\sin(ax)| = \frac{1 - \cos(a\pi)}{a \pi} - \frac{2a}{\pi} \sum_{n=0}^{\infty} \frac{(1-(-1)^{n} \cos(a\pi))}{n^{2}-a^{2}} \ \cos(nx) \end{align} or \begin{align} |\sin(ax)| = \frac{\sin^{2}\left(\frac{a\pi}{2}\right)}{2 a \pi} - \frac{2a}{\pi} \sum_{n=0}^{\infty} \frac{(1-(-1)^{n} \cos(a\pi))}{n^{2}-a^{2}} \ \cos(nx). \end{align}

Now, when $a=1$ this reduces to \begin{align} |\sin(x)| &= \frac{2}{\pi} - \frac{2}{\pi} \sum_{n=0}^{\infty} \frac{1+(-1)^{n}}{n^{2}-1} \ \cos(nx) \\ &= \frac{2}{\pi} - \frac{4}{\pi} \sum_{n=0}^{\infty} \frac{\cos(2nx)}{4n^{2}-1}. \end{align} In order to evaluate the series in question let $x = \pi/2$ for which the Fourier series is reduced to \begin{align} |\sin(\pi/2)| &= \frac{2}{\pi} - \frac{4}{\pi} \sum_{n=0}^{\infty} \frac{\cos(n \pi)}{4n^{2}-1} \\ &= \frac{2}{\pi} + \frac{4}{\pi} \sum_{n=0}^{\infty} \frac{(-1)^{n-1}}{4n^{2}-1}. \end{align} which leads to \begin{align} \sum_{n=0}^{\infty} \frac{(-1)^{n-1}}{4n^{2}-1} = \frac{\pi - 2}{4}. \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.